The fabrication and study on development for the activation circuit using sound sensor. / Mohd Hafeez Kasman - Kasman, Mohd Hafeez (2010)
The study is about to control or activate the camera system using the sound sensor circuit. It is include developing the sound sensor circuit and doing the experiments to know the characteristics of the sound sensor. The camera with sound sensor switch will work best when the characteristic is known for any modification. So two experiments are carried out to the circuit. First is to know the minimum and maximum voltage produced by the circuit. Hence the minimum voltage is 0 volts and the highest is 5 volts. It is influenced by the voltage supplied, sound intensity, and the distance of the source. Second is to know the range of sound that can captured by the microphone. The microphone can capture sound in heart - shape only. It is work best when the source of sound is exactly in front of the microphone.